A comparison of the effects of factor XII deficiency and prekallikrein deficiency on thrombus formation. Issue 140 (April 2016) - Kokoye, Yasin; Ivanov, Ivan; Cheng, Qiufang; Matafonov, Anton; Dickeson, S. Kent; Mason, Shauna; Sexton, Daniel J.; Renné, Thomas; McCrae, Keith; Feener, Edward P.; Gailani, David
Abstract: Studies with animal models implicate the plasma proteases factor XIIa (FXIIa) and α-kallikrein in arterial and venous thrombosis. As congenital deficiencies of factor XII (FXII) or prekallikrein (PK), the zymogens of FXIIa and α-kallikrein respectively, do not cause bleeding disorders, inhibition of these enzymes may have therapeutic benefit without compromising hemostasis. The relative contributions of FXIIa and α-kallikrein to thrombosis in animal models are not clear. We compared mice lacking FXII or PK to wild type mice in established models of arterial thrombosis. Wild type mice developed carotid artery occlusion when the vessel was exposed to a 3.5% solution of ferric chloride (FeCl3 ). FXII-deficient mice were resistant to occlusion at 5% FeCl3 and partially resistant at 10% FeCl3 . PK-deficient mice were resistant at 3.5% FeCl3 and partially resistant at 5% FeCl3 . Mice lacking high molecular weight kininogen, a cofactor for PK activation and activity, were also partially resistant to thrombosis at 5% FeCl3 . Induction of carotid artery thrombosis with Rose Bengal was delayed in FXII-deficient mice compared to wild type or PK-deficient animals. In human plasma supplemented with silica, DNA or collagen to induce contact activation, an antibody to the FXIIa active site was more effective at preventing thrombin generation than an antibody to the α-kallikrein active site. Similarly, the FXIIa antibody was more effective at reducing fibrin formation in human blood flowing through collagen coated-tubes. The findings suggest that inhibitors of FXIIa will have more potent anti -thrombotic effects than inhibitors of α-kallikrein. Highlights: Factor XII (FXII) and prekallikrein (PK) contribute to thrombosis in mice. FXII deficient mice are more resistant to thrombosis than are PK deficient mice. Inhibiting FXII or PK affects reciprocal FXII-PK activation. FXII inhibition has a greater effect on coagulation than PK inhibition in plasma.